The relationship between noise annoyance, emotional labor and burnout in operating-room nurses: A protocol for cross-sectional study - Yizhi Zhang; Yan Chen; Jiaqing Rao; Qingjiao Guo; Jing Ou-yang; Shasha Luo; Ying Gu (PLoS ONE, 2025)
Operating room nurses may experience occupational burnout brought by noise annoyance during which emotional labor may act as a moderating factor between the two. The aims of this study are: (1) to investigate the independent correlation between noise annoyance and burnout among operating room nurses; (2) to explore the relationship between noise annoyance, emotional labor, and burnout. This study, a cross-sectional study design, is being conducted in Guizhou province, China. The Chinese version of the noise annoyance, emotional labor and burnout scale will be used to assess the current situation of the samples, and the data will be collected using paper questionnaires and electronic questionnaires. Additionally, the Pearson or Spearman rank correlation coefficients will be involved in correlation analyses. Multiple linear regression analysis will be also carried out to produce β-coefficients with 95% confidence intervals. A nonparametric, bias-corrected 95% bootstrapped confidence interval with 5,000 bootstrap iterations will help to determine the importance of mediating effects. The trial registration number is ChiCTR2300068414.